Case ReportIdiopathic eruptive macular pigmentation – a rare pigmentary disorder - Komorowska, Olivia; Szczerkowska-Dobosz, Aneta; Roziewska, Dominika; Czapiewski, Piotr (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Skin pigmentation disorders are frequent problems in dermatological practice. They have a heterogeneous aetiology and clinical picture, and demand a flexible therapeutic approach. We present a case of a 10-year-old boy with idiopathic eruptive macular pigmentation. It is a rare chronic entity which causes only an aesthetic defect and demands no treatment. Key words: idiopathic eruptive macular pigmentation, ashy dermatosis, macules.